SiO–Sn2Fe@C composites with uniformly distributed Sn2Fe nanoparticles as fast-charging anodes for lithium-ion batteries - Hanyin Zhang; Renzong Hu; Sirui Feng; Zhiqun Lin; Min Zhu (eScience, 2023)
SiO-based materials represent a promising class of anodes for lithium-ion batteries (LIBs), with a high theoretical capacity and appropriate and safe Li-insertion potential. However, SiO experiences a large volume change during the electrochemical reaction, low Li diffusivity, and low electron conductivity, resulting in degradation and low rate capability for LIBs. Here, we report on the rapid crafting of SiO–Sn2Fe@C composites via a one-step plasma milling process, leading to an alloy of Sn and Fe and in turn refining SiO and Sn2Fe into nanoparticles that are well dispersed in a nanosized, few-layer graphene matrix. The Sn and Fe nanoparticles generated during the first Li-insertion process form a stable network to improve Li diffusivity and electron conductivity. As an anode material, the SiO–Sn2Fe@C composite manifests high reversible capacities, superior cycling stability, and excellent rate capability. The capacity retention is found to be as high as 95% and 84% at the 100th and 300th cycles under 0.3 ​C. During rate capability testing at 3, 6, and 11 ​C, the capacity retentions are 71%, 60%, and 50%, respectively. This study highlights that this simple, one-step plasma milling strategy can further improve SiO-based anode materials for high-performance LIBs.